PENGGUNAAN LEMBAR KERJA SISWA (LKS) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS XI SMAN 8 PEKANBARU - Asnitawati Asnitawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2018)
Biology learning results of students in class XI have not shown optimal on material that discusses the physiological functions of human organs. From the observations obtained data that the teacher learning process using Student Worksheets prepared by the Subject Teachers' Consultation (MGMP), has not used the scientific approach. This has triggered the writer to conduct classroom action research aimed to improve students biology learning results in class XI by using worksheets based on Student Centered Learning are arranged in such a way as to meet the learning approach of science using step 5 M. This class action research procedure used two cycles, at the end of each cycle the students' daily tests are performed to see the increase in learning results that occur. After the cycle I action, the average student learning results were 71.47, and it increased in cycle II to 76.31, so it can be concluded that the use of Student Worksheets Based on Student Centered Learning can improve the biology learning results of the second year students of SMA Negeri 8 Pekanbaru.